2015
DOI: 10.1007/s00420-015-1066-6
|View full text |Cite
|
Sign up to set email alerts
|

The healthy worker effect: Do health problems predict participation rates in, and the results of, a follow-up survey?

Abstract: The health status of participants at baseline seems to have little impact on the external and internal validity of the follow-up assessment in prospective survey research. Hence, the findings provide little support to the HWE as a potential bias in prospective studies within occupational health research. A limitation of the study is that the findings do not inform about the impact of the HWE on participation in the baseline assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…‘healthy worker effect’). However, recent findings from a two-wave study indicate few differences in baseline somatic and mental health problems in responders vs. non-responders 41 . Despite low education level predicting dropout, baseline associations between health and work factors remained the same in responders and non-responders.…”
Section: Discussionmentioning
confidence: 80%
“…‘healthy worker effect’). However, recent findings from a two-wave study indicate few differences in baseline somatic and mental health problems in responders vs. non-responders 41 . Despite low education level predicting dropout, baseline associations between health and work factors remained the same in responders and non-responders.…”
Section: Discussionmentioning
confidence: 80%
“…There was no statistical significance of SMR for increasing total and solid cancer mortality risk in uranium facility workers when combined with nuclear power plant and medicinal research (49), and the health worker effect was observed. This effect consists of three components, namely the health worker survival (17)(18)(19), health worker exposure (52)(53)(54)(55) and health worker selection (55,56) effects in occupational exposure epidemiology, and leads to the selection of a working population that is healthier compared with the general population. As a result, the observed SMR of the cancers of interest in this study was lower compared with the control population.…”
Section: Follow-up --------------------------------------------------mentioning
confidence: 99%
“…With help from SIA and Statistics Sweden, the following three cohorts were extracted from the study base to obtain groups with and without recent sickness absence (see also figure 1 and ref. 28 for more details): 15 April 2008 (n=6140 in the employee cohort and n=4240 in the non-employee cohort), as the survey ideally should be conducted as close as possible to the current absence episode. In the employee cohort, the total sampling frame was invited to participate (n=6140), whereas a random sample of the non-employee-sampling frame was invited (n=990).…”
Section: Target Population and Cohorts In Hapmentioning
confidence: 99%
“…32 Second, the use of registries reduced common methodological problems such as recall bias and missing responses. 15 Third, since the registry data are based on financial reimbursement from the SIA, they are considered to be accurate and reliable. Finally, examining sickness absence several years before the survey is a particular advantage when studying selection by sickness absence, as the phenomenon on the one hand is common, with a 1 year cumulative incidence of 11.3% in the working population in Western Sweden in 2008 33 and, on the other hand, in some cases is prolonged and recurrent.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation